Terrorism Revisited
XIII, 223 p.
Keywords: This book develops a conceptual approach to understanding the face of contemporary terrorism as manifested in the recent attacks in Mumbai and Paris. By analyzing the historical evolution of terrorism and by offering case studies on different forms of terrorism in South Asia and elsewhere, the authors shed new light on the political strategies behind terrorist attacks, as well as on the motivations of terrorists. The case studies explore the redefinition of terrorism by the Iranian Islamic revolution, the spread of terrorism in Sunni Islam, the national jihadism in Pakistan, anti-Semitism as a main factor behind fanatical terrorist ideologies, and the case of the Tamil Tigers. "Redefining terrorism is a dynamic story that provides readers with intrigue and clarity to the ever-evolving threats that we face as a nation and as a global community. The authors masterfully navigate through the intricate maze of global terrorism bringing an overwhelming dose of reality through his usage of real life, gripping experiences. Through this book military and intelligence analysts and policy makers alike will gain first-hand knowledge about not only what the world looks like today but a glimpse into the future." US Congressman Pete Sessions.